Bridging Cultures: Preparing Non-Indigenous Teachers to Teach Indigenous Epistemology in a Rural Public School - Moreton, Simonjay (Scholarship@Western, 2023)
This Organizational Improvement Plan looks to lay the framework to help non-Indigenous teachers challenge negative Indigenous stereotypes, overcome their fear of unintentionally culturally appropriating an Indigenous culture, and be able to effectively integrate Indigenous content into course curriculum to fulfill the First Nations, Metis and Inuit requirement of the Alberta Teacher Quality Standards. This framework leverages the Anishinaabe Medicine Wheel in conjunction with the ADKAR change model to facilitate a cultural change at Ranchlands Public School, a small rural school situated in Southern Alberta. As the Principal, I intend to implement a transformational change that will institute a shift in mindset by connecting Indigenous Elders with non-Indigenous teachers through a blended online and on-land learning platform. Engaging Indigenous Elders in sharing their knowledge, usually through the traditional art of storytelling and/or mentorship, helps to minimize the potential for cultural appropriation by non-Indigenous teachers. With the Elder stepping into the role of ‘instructor’, and the non-Indigenous classroom teacher assuming the role of ‘pupil’, there will be a natural shift in learning towards recognizing the contributions and knowledge systems of other cultures. It is by interlacing Indigenous and Euro-settler cultures into the educational framework and culture of a class that students will begin to build a respect for other cultures; that our Indigenous students will feel valued as their traditional Indigenous knowledge is being recognized in the school; and in time, both knowledge systems, although distinct, will be used to help students explore the prescribed curriculum at a deeper level.